FILM BASED LEARNING: UPAYA PENINGKATAN MOTIVASI MAHASISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - Puji Lestari (Khazanah Pendidikan, 2009)
The use of media in the learning process should be base on an objective criterion which includes the learning goal (basic and standard competence), the learning activities and evaluation. This research is class experience in solving the decreasing motivation and enthusiasm. As a medium in teaching civics, a film should be selected on the basis of its contens. The research was divided into two cycles, of which the result was analysed qualitatively with categorical and functional parameter through interactive model. The first cycle gave the expected results but needed to maximized. After film was used, 64 % of the students showed an improved motivation. This could be seen from their participation in the class discussion. In the second cycle, the learning process showed its maximum result, in which 96 % of the students gave their full participation in the lesson. Key words: film, learning, motivation.